SNRPB2 facilitates esophageal squamous cell carcinoma oncogenesis and progression via E2F4 stabilization - Xu, Feng; Zhu, Chen-Cheng; Lu, Chen; Ning, Guang-Yao; Zhang, Ren-Quan (Frontiers in Immunology, 2025)
IntroductionEsophageal cancer (ESCA) is a highly aggressive malignancy with poor prognosis. Small nuclear ribonucleoprotein polypeptide B2 (SNRPB2) is a core component of the spliceosome involved in pre-mRNA splicing. However, its role in tumor development and progression remains largely unclear. This study aimed to evaluate the clinical relevance and prognostic value of SNRPB2 in ESCA.MethodsSNRPB2 mRNA expression and genetic alterations were analyzed using GEPIA2 and cBioPortal. Protein expression was assessed by immunohistochemistry in paraffin-embedded esophageal squamous cell carcinoma (ESCC) tissues. Functional assays in ESCC cell lines were conducted to determine the biological role of SNRPB2. Immune-related and functional analyses were performed using TIMER, TISIDB, TISCH, Gene Ontology (GO), and Gene Set Enrichment Analysis (GSEA). Cycloheximide (CHX) chase assays were used to assess protein stability.ResultsSNRPB2 mRNA was upregulated in ESCA and associated with tumor progression and poor prognosis. Immunohistochemistry confirmed high SNRPB2 protein expression in ESCC, correlating with vessel carcinoma embolus, lymph node metastasis, clinical stage, and tumor grade. SNRPB2 knockdown significantly inhibited ESCC cell proliferation, migration, and invasion in vitro and in vivo. GSEA indicated that SNRPB2 suppresses the Rb/E2F pathway. Mechanistically, SNRPB2 stabilized E2F4 protein by preventing its proteasomal degradation, and E2F4 overexpression reversed the tumor-suppressive effects of SNRPB2 silencing. Immune analyses showed that SNRPB2 expression correlated with increased infiltration of activated CD8+ T cells, γδ T cells, dendritic cells, and monocytes, as well as immune-related genes including PDCD1, CD274, CTLA4, HLA-DRA, and B2M. These findings suggest a dual role for SNRPB2 in promoting tumor progression and modulating the immune microenvironment in ESCA.ConclusionSNRPB2 promotes ESCC progression by stabilizing E2F4 and regulating cell cycle genes. It is also associated with immune infiltration and gene expression in ESCA. SNRPB2 may serve as a prognostic biomarker and potential therapeutic target in esophageal cancer.